Internet users as vulnerable and at-risk human subjects: reviewing research ethics Law for technical internet research - Zevenbergen, B (2020)
Computer science research is subjected to similar research ethics reviews as other research disciplines. However, the nature of computer science research, especially on the Internet, is vastly different from other forms of research. Many data points are the end devices owned and operated by human Internet users, though they are often not considered as being human subjects. This thesis addresses the nature of computer science research, and examines the extent to which the ethics of care might be a useful model to assess the ethics of computer science research. This responds the nature of data subjects as being relatively vulnerable humans who do not understand how their informational environment is changed due to research conducted on their devices and the networks to which they connect.